Experimental study of fibre-reinforced interlocking mud bricks under compressive test. Issue 4 (18th August 2020) - Muhammad; Saleem, Muhammad Azhar; Kazmi, Syed Minhaj Saleem; Munir, Muhammad Junaid
Abstract : The focus of this study was to develop manually compressed interlocking mud bricks and study their compressive strength. For this purpose, mud bricks were manufactured incorporating wheat straw (1–4% by weight of soil) and rice husk (1–5% by weight of soil). Furthermore, mud bricks were also manufactured using lime (12%, 15% and 19% by weight of soil) and a combination of wheat straw and rice husk, named straw husk (1–4% by weight of soil) as an additive. To investigate the strength and failure pattern of interlocking mud bricks, compressive strength testing was performed. The control mud bricks showed shrinkage cracks, but no signs of shrinkage cracking were observed in specimens incorporating fibres (wheat straw, rice husk and straw husk). A decrease in compressive strength was observed with increasing content of fibres in the mud brick specimens. However, interlocking mud bricks incorporating fibres fulfilled the minimum strength requirements of different standards for mud bricks. A decrease in compressive strength of the mud bricks was also observed when using lime as an additive. Nevertheless, interlocking mud bricks incorporating lime (up to 19%) satisfied the minimum strength requirement of the Turkish standard. Therefore, interlocking mud bricks incorporating fibres and lime can be used in earthen construction, leading towards sustainable structures.